Experience and Nature - Dewey, John 1859-1952 (New York Dover, 1958)
Dewey believes that the method of empirical naturalism presented in this volume provides the way, and the only way by which one can freely accept the standpoint and conclusions of modern science. Contents: experience and philosophic method; existence as precarious and as stable; nature, ends and histories; nature, means and knowledge; nature, communication and as meaning; nature, mind, and the subject; nature, life and body-mind; existence, ideas and consciousness; experience, nature and art; existence value and criticism.
Unabridged republication of the second edition, 1929
Originally published in 1925
Keywords: 20th Century (1901-2000); Philosophy; USA